Mooring facility templates and forms (compliance certificate / schedule of works / appropriately experienced person) - (:unkn) unknown (Great Barrier Reef Marine Park Authority, 2024)
Moorings forms, including Moorings Compliance Certificate, Schedule of Works and Appropriately Experienced Person forms. For more guidance on facilities, including moorings, refer to the 'Checklist - facility permission' at: https://elibrary.gbrmpa.gov.au/jspui/handle/11017/3843; and 'A guide for current permit holders: essential reading for Great Barrier Reef Marine Parks permit holders' available in this repository at https://hdl.handle.net/11017/3812.
Keywords: Permits; Mooring buoys; Managing Multiple Use; Permits and assessments; mooring; moorings; facility; compliance certificate; schedule of works; experienced person; Reef-wide